KEBIJAKAN PENETAPAN RUTE PENERBANGAN PADA ERA ASEAN OPEN SKY - Ira Rahman; Husni Hasan; Francis Tantri; Indra Setiawan (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2017)
The objective of this research is to analyze the evaluation of flight route policies, through program effectiveness, program adequacy, program distribution program that is enjoyed by all the aviation stakeholder and responsiveness and to recommend design improvement (roadmap) on flight route policies in accordance to the ASEAN Open Sky policy for the national carriers to be competitive. Research methods used are qualitative description with USG (Urgency, Seriousness, Growth) approach or Issue Priority Matrix, investigation result on the flight path policies evaluation. The research used purposive sampling technique to determine the informant. The study result provides an overview of the preparation of improvement actions based on program evaluation through the establishment of medium term roadmap which consists; a) Grand Design disposition that regulate Indonesian airspace as state asset that has strategic value, b) Development of route connectivity functions, where national carrier must develop Global Distribution System functions. These GDS functions must be enhanced to provide support for assisting the airlines distribution process, simplifying airlines ticket booking, and minimalizing investment cost. c) Assessment of all Civil Aviation Safety Regulation (CASR) associated with Air Traffic Management (ATM), as well as d) developing e-business functionality that provides support for services.